AI-based energy modelling and forecast for heating, ventilation and air conditioning (HVAC) systems - Lim, Celia Kar Cheng (Nanyang Technological University, 2024)
The building sector is a significant energy consumer globally, with Heating, Ventilation, and Air Conditioning (HVAC) systems accounting for 40-60% of energy consumption in commercial buildings. Despite efforts under Singapore's Green Plan 2030 to reduce energy use, the country's commercial building energy consumption has grown by 25% from 2008 to 2019 and is projected to rise further. Traditional HVAC systems face challenges in incorporating external factors like weather and occupancy patterns, which affect energy efficiency.